Corporate social responsibility information and involvement strategies in controversial industries. (23rd August 2018) - Vollero, Agostino; Conte, Francesca; Siano, Alfonso; Covucci, Claudia
Abstract: This paper assesses how companies belonging to controversial and non‐controversial industries differ in their adoption of corporate social responsibility (CSR) information and involvement strategies. Drawing on legitimacy and stakeholder theories, a thematic content analysis of the websites of companies listed in the Dow Jones Sustainability Word Index is used to establish a set of measures for CSR communication strategies aimed at fostering stakeholder engagement. Companies in controversial industries are found to be more likely to adopt a CSR information strategy than those in non‐controversial industries but do not attempt to create stakeholder involvement. The results highlight the importance for communication managers in controversial organizations of considering information strategies as a meta‐level of engagement and of implementing an involvement strategy to mitigate the level of controversy. The study offers a wider conceptualization of the business activities of controversial industries and contributes to the debate on stakeholder engagement for organizational legitimacy.